PERLINDUNGAN KONSUMEN TERHADAP TABUNG OKSIGEN YANG TIDAK MEMENUHI STANDAR NASIONAL INDONESIA (SNI) - Amalia, Frista (Lex Journal: Kajian Hukum & Keadilan, 2022)
The use of oxygen cylinders in a pandemic is necessary for health, but circulating oxygen cylinders that do not meet the Indonesian National Standard (SNI) are dangerous to health. So the government needs to protect consumers. The problems discussed in this study are: regulation of the use of oxygen cylinders for health; the responsibility of business actors who produce oxygen cylinders do not meet SNI; sanctions for business actors who produce oxygen cylinders that do not meet SNI. The research method is normative legal research, with a statutory and conceptual approach. The results of the research are: The Indonesian National Standard in the use of oxygen cylinders for health is regulated in Article 196 of Law Number 36 of 2009 and Article 24 paragraph (1) and Article 25 of Law Number 20 of 2014; Business actors who produce oxygen cylinders that do not meet the Indonesian National Standard must be responsible for their mistakes, due to losses suffered by patients or even causing the death of the patient; Business actors who produce and trade oxygen cylinders that do not meet the Indonesian National Standards can be sanctioned according to Article 62 paragraph (1) of the UUPK with criminal sanctions and fines, also based on Article 106 of the Health Law Keywords: Consumer Protection, Oxygen Cylinder, Indonesian National Standard